Credit Chains and Sectoral Comovement : Does the Use of Trade Credit Amplify Sectoral Shocks? - Raddatz, Claudio (World Bank, Washington, DC, 2012)
This paper provides evidence of the presence and relevance of a credit-chain amplification mechanism by looking at its implications for the correlation of industries. In particular, it tests the hypothesis that an increase in the use of trade-credit along the input-output chain linking two industries results in an increase in their correlation. The analysis uses detailed data on the correlations and input-output relations of 378 manufacturing industry-pairs across 44 countries with different degrees of use of trade credit. The results provide strong support for this hypothesis and indicate that the mechanism is quantitatively relevant.